System of Equations Using the Substitution Method with Nonlinear Equations
Solve System of Equations Substitution Method - Part 2 - How it Works - Video
Which Variable to Solve For
Which Variable to Solve For:
We have 4 options when dealing with 2 equations in a system of equations. We can solve for x or y for the nonlinear equation or we can solve for x or y for the linear equation. Each one has their own pros and cons, and that depends on you.
We are going to use x = 2y + 3.
Example 1 - Substitute
Example 1 Substitute:
Here we have solved for the variable x in x - 2y = 3 and our result is x = 2y + 3. We have to substitute this equation into our other equation, x + y2 = 6.
x + y2 = 6
(2y - 3) + y2 = 6
Original
We substituted
Example 1 - Solve for the 1st Variable
Example 1 Solve for the 1st Variable:
Here we have solved for the variable x in x - 2y = 3 and our result is x = 2y + 3. We have to substitute this equation into our other equation, x + y2 = 6.
x + y2 = 6
(2y - 3) + y2 = 6
y2 + 2y - 3 = 6
y2 + 2y - 9 = 0
(y + 3)(y - 1) = 0
Original
We substituted
Rearrange terms
Subtracted 9 to both terms
Factor
We have factored and now we have two equations y + 3 = 0 and y - 1 = 0 so y = -3 and y = 1.
Example 1 - Plot 1st Equation
Example 1 Plot 1st Equation:
We have factored and now we have two equations y + 3 = 0 and y - 1 = 0 so y = -3 and y = 1.
Now that we know y = -3 and y =1. We can substitute in either question to find the x part of the ordered pair. Here we chose the linear equation.
x - 2y = 3
x - 2 * (-3) = 3
x + 6 = 3
x = -3
Substituted -3
Multiplied
Added -6 to both sides
x - 2y = 3
x - 2 * (1) = 3
x - 2 = 3
x = 5
Substituted 1
Multiplied
Added 2 to both sides
So our points are (-3, -3) and (5, 1).
Example 1 - Plot 2nd Equation
Example 1 Plot 2nd Equation:
We know the points (-3, -3) and (5, 1) are also true for our 2nd equation. We know that is a parabola, which means we need our vertex. To find our vertex since we have a sideways parabola, we can use the formula y = -b / (2a). Which one is a? Which one is b? We look at the standard form, x = ay2 + by + c. We have x = -1y2 + 0y + 6, so a = -1, b = 0, and c = 6.
y = -b / [2a]
y = - (0) / [2 * (-1)]
y = 0
Substituted a and b
Multiplied
x = -y2 + 6
x = -(0)2 + 6
x = 6
Substituted a and b
Multiplied and added
So x is 6, which means our point is (6, 0). Now we can graph our sideways parabola, and our solutions are the points (-3, -3) and (5, 1)